Innovation Digital and Virtual Reality Based Instructional Design for High School Students - Fatqurhohman Fatqurhohman; Nia Wahyu Damayanti; Xiaoli Chen (Ihsan Cahaya Pustaka, 2025)
This study introduces an innovative instructional design integrating digital technology and virtual reality (VR) to enhance high school students’ mathematics learning. The research involved tenth-grade students as end-users and expert validators, including digital media specialists, subject matter experts, and instructional design professionals. Using a research and development approach, data were collected through expert validation questionnaires, classroom observations, and student interviews. Quantitative data were analyzed descriptively with Aiken’s content validity coefficient, while qualitative data underwent thematic analysis. Findings reveal that the VR-based instructional design achieved high validity (Tc>Tt) and effectively improved students’ conceptual understanding, engagement, and motivation in mathematics. The instructional design facilitated engaging and interactive learning experiences that made abstract concepts more accessible for students to grasp. Findings highlight the value of integrating virtual reality and digital media in building student-centered learning environments, with practical implications for improving mathematics teaching in secondary schools and fostering innovation in instructional design.